Self-Control sebagai Moderasi antara Pengelolaan Keuangan dan Financial Attitude terhadap Perilaku Menabung Mahasantri KH. Mas Mansur Universitas Muhammadiyah Surakarta - Nikmah, Zulfa Izzatun; Ulfatun, Titik (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the effect of financial management and financial attitude on saving behavior, with self-control as a moderating variable among KH. Mas Mansur students at Muhammadiyah University of Surakarta. This study used a quantitative approach. Sampling was conducted using a random sampling technique, where each person in the entire target population has an equal opportunity to be selected. The study sample consisted of 140 respondents from a population of 220, namely students living at the KH. Mas Mansur Student Islamic Boarding School at Muhammadiyah University of Surakarta. Data collection used a questionnaire sent via Google Forms. Indicators were measured using a Likert scale, then analyzed using multiple linear regression. The results of this study revealed that simultaneously and partially, there was a significant influence between financial management and financial attitude variables on saving behavior among KH. Mas Mansur students at Muhammadiyah University of Surakarta. However, the self-control variable was not able to moderate the influence of financial management and financial attitude variables on saving behavior among KH. Mas Mansur students at Muhammadiyah University of Surakarta